Kendali Pid Pada Robot Manual Menggunakan Komunikasi Nirkabel - Widiantara, Helmy; Ihyaudin, Ihyaudin; Firmansyah, Danang; Sugiharto, Achmad (Journal JCONES, 2012)
At this time, the main problems encountered in robot control robot motion is a matter that is less refined in its movement relates to how the robot moves according to what has been ordered by the user, either in the form of a command position, velocity and acceleration. In addition, to control the robot manually, most still use a cord and less efficient in its use. So that the user (user) must use a long cable so that it can interfere with the motion of the robot. This thesis aims to simplify the user to control a robot using wireless communication with the manual joystick as a controller of the robot is implemented with wireless technology for transmitting data to the robot manually using the communication module Xbee-Pro, a minimum system of ATMega 32, a series of manual robot consisting of the motor driver module DC and the drive wheel. Joystick in this case has been integrated with the minimum system & Xbee-Pro transmitter (Tx), while the robot is connected with the minimum system manual & Xbee-Pro receiver (Rx), so the joystick can control the movement of the robot wirelessly. To deal with manual control of robot movement, the final task is to use PID control algorithm in the control system. The search process is the result of the constant analysis of the characteristics of the motor is implemented using a microcontroller ATMega 32 of the data obtained from the rotary encoder. Research has been done, the robot can manually take orders from the user with the form of a command position, velocity and acceleration accurately and run smoother by using a constant value of KP = 1, KI = 0.00004 & KD = 0.00002 which is the result of analysis of the characteristics of the motor charts with the value of KP, KD, and KI has the author tried. Robot can manually generate a minimum of actual speed and the maximum 125Rpm 98Rpm averaging time of 1s stable. In this experiment the best result is the value of the actual speed of 125 rpm with a time of 0.8 seconds is stable. Development of wireless communication technology to replace communication with the media cable robot applied in this manual runs well on 1-10 meter range in a confined space conditions and the range of 1-100 meters in open space. In this situation, as long as the position Xbee Xbee Pro Pro Tx and Rx in a horizontal state (point to point) with a bit of an obstacle then the distance will be more distant. But if there is obstruction of the building it is likely that the data transmission can also be losses even data can not be accepted by the receiver.